Pericapsular Nerve Group Block of the Hip Joint After Arthroplasty - S. V. Zhuravel; E. Y. Bezverkhaya; E. A. Korotkova; A. M. Fayn (Неотложная медицинская помощь, 2022)
We report a case of postoperative pain relief in a patient after total cement arthroplasty of the right hip joint in the early postoperative period. Pericapsular nerve group block (PENG-block) of the hip joint was suggested to provide adequate pain relief and reduce the risk of postoperative complications. This clinical case shows an example of effective pain relief in a patient in the early postoperative period after reconstructive plastic restoration of the right hip joint, performed for a fracture of the femoral neck. Severe pain syndrome, restriction of movements, forced position and volume of surgical intervention are risk factors for the development of thromboembolic complications. According to the literature, the incidence of thromboembolic complications after total cemented hip arthroplasty varies from 9.3 to 20.7%. Our observation indicates that pericapsular block of the hip joint is an effective method of pain relief in the early postoperative period after total hip replacement.